Downtown Fresno Nuclear Freeze March to and Vigil in Courthouse Breezeway - Watkins, Howard::::::::: (1982)
?, Ruth Albright holding sign: Win With Love; Ken Clarke, Karen Humphrey Fresno Hilton Hotel in background